If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(4) + log(x + -1) = log(3x) Reorder the terms for easier multiplication: 4glo + log(x + -1) = log(3x) Reorder the terms: 4glo + glo(-1 + x) = log(3x) 4glo + (-1 * glo + x * glo) = log(3x) 4glo + (-1glo + glox) = log(3x) Combine like terms: 4glo + -1glo = 3glo 3glo + glox = log(3x) Remove parenthesis around (3x) 3glo + glox = glo * 3x Reorder the terms for easier multiplication: 3glo + glox = 3glo * x Multiply glo * x 3glo + glox = 3glox Solving 3glo + glox = 3glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-3glox' to each side of the equation. 3glo + glox + -3glox = 3glox + -3glox Combine like terms: glox + -3glox = -2glox 3glo + -2glox = 3glox + -3glox Combine like terms: 3glox + -3glox = 0 3glo + -2glox = 0 Factor out the Greatest Common Factor (GCF), 'glo'. glo(3 + -2x) = 0Subproblem 1
Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(3 + -2x)' equal to zero and attempt to solve: Simplifying 3 + -2x = 0 Solving 3 + -2x = 0 Move all terms containing g to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 0 + -3 -2x = 0 + -3 Combine like terms: 0 + -3 = -3 -2x = -3 Add '2x' to each side of the equation. -2x + 2x = -3 + 2x Combine like terms: -2x + 2x = 0 0 = -3 + 2x Simplifying 0 = -3 + 2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3x+2y-4x+3= | | (9+7i)(8-3i)= | | 8z+5=1 | | 2y+5x=77 | | 4x+7-x=13 | | -7x-10=-136 | | 12x-3x^2=12 | | 9(t-3)+3t=6(2t+4)-12 | | a+2a+3a=12 | | -12(x-1)=4(x+9) | | 4x^2-16x-208=0 | | 8x+4y+6u+2z=-16 | | x^3-x^2-3x-1=0 | | 29-11=30-x | | 95-63=x-60 | | 8x-7=-10+9x | | 8x-4x-20=4 | | 89-45=90-x | | 2(2a+2)=11+3a | | 37-21=x-24 | | x-a+2=2ax-3x | | 7z-11=43+z | | a^2+11a=12 | | ln(2x+-9)=0 | | 3s^2+28x-3=0 | | F(x)=x^2-15x+15 | | 43-26=40-x | | 5.2x=31 | | 17x+12=17x-12 | | 5.2x=32 | | (1)(2)y-7=(1)(5)y | | 56-21=x-20 |